Pengaruh Pijat Oksitosin terhadap Kelancaran Produksi Air Susu Ibu pada Ibu Post Sectio Caesarea Hari Ketiga di wilayah Kerja Puskesmas Taliwang - Nia Firdianty Dwiatmojo; Nurhayati Nurhayati; Endah Sulistyani; Ni Nyoman Santi Tri Ulandari; Wahyu Cahyono; Chinta Virahan Akrabiatullah; Robiatul Adawiyah (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Bacground: Sustainable Development Goal number 3 regarding a healthy and prosperous life is an effort to reduce child mortality with the Gold Standard of Baby Food, providing exclusive breast milk containing nutrients according to the baby's needs which is useful for the baby's growth and development. It is known that post-cesarean section mothers on the third day at the Asy-Syifa Regional General Hospital, West Sumbawa, experienced irregularities in breast milk production, which was an obstacle to implementing early breastfeeding initiation. Objective: This study aims to determine the effect of oxytocin massage on the smooth production of breast milk (ASI) in mothers post Sectio Caesarea on the third day at the Asy-Syifa Regional General Hospital, West Sumbawa. Method: this research is a quantitative research using a non-probability technique method with purposive sampling one group pre-test post-test, the sample this research used was 40. Result: The results before being given oxytocin massage showed that breast milk was smooth, the highest mother in the non-fluent category was 38 respondents (95.0%) and the lowest was fluent as many as 2 respondents (5.0%) and after being given oxytocin massage the breast milk flowed smoothly, the highest mother with the fluent category was 35 respondents (87.5%) and not fluent as many as 5 respondents (12.5% ). Conclusion: there is an effect of oxytocin massage on the smooth production of breast milk post cesarean section at the Asy-Syifa Regional General Hospital, West Sumbawa, proven by a T Test value of 0.000 (p>0.005).